2009
DOI: 10.1002/jez.b.21265
|View full text |Cite
|
Sign up to set email alerts
|

Chick tooth induction revisited

Abstract: Teeth have been missing from Aves for almost 100 million years. However, it is believed that the avian oral epithelium retains the molecular signaling required to induce odontogenesis, and this has been widely examined using heterospecific recombinations with mouse dental mesenchyme. It has also been argued that teeth can form from the avian oral epithelium owing to contamination of the mouse mesenchyme with mouse dental epithelial cells. To investigate the possibility of tooth formation from chick oral epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous rough estimates have suggested that edentulism in Neornithes was reached within a narrow possible time interval, generally between 100 and 80 Ma [5,6,12,20]. By contrast, we notice that the available data allow a wider possible interval between circa 125 Ma and 65.5 Ma.…”
Section: Timing Of Tooth Lossmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous rough estimates have suggested that edentulism in Neornithes was reached within a narrow possible time interval, generally between 100 and 80 Ma [5,6,12,20]. By contrast, we notice that the available data allow a wider possible interval between circa 125 Ma and 65.5 Ma.…”
Section: Timing Of Tooth Lossmentioning
confidence: 63%
“…Therefore, the true teeth obtained through recent mouse mesenchyme-chicken epithelium recombinations [20] are likely to result from contamination by mouse epithelium, because chick epithelium is definitely unable to produce enamel. However, the shape of some teeth obtained by these authors surprisingly resembles Archaeopteryx or alligator teeth [20]. This might result from conserved dental morphogenetic determinants in the chick epithelium.…”
Section: Diversion Of Gene Functionmentioning
confidence: 99%
“…One inevitable question that arises is whether it is possible to induce tooth development, or to “turn teeth back on” in modern turtles. Researchers have partially rescued odontogenesis in chicks (Kollar and Fisher, ; Kollar and Mina, ; Chen et al, ; Mitsiadis et al, ; Mitsiadis et al, ; Cai et al, ), although the potential for enamelization may be small due to the loss of enamel‐specific genes from the chick genome (Sire et al, ). Tooth loss in turtles occurred in the Jurassic (201.6–145.5 Ma), much longer ago than tooth loss occurred in any mammals (Cenozoic) or in birds (Cretaceous).…”
Section: Discussionmentioning
confidence: 99%
“…5), notably trigger fish (Soule, 1969), extinct mosasauroid lizards (Caldwell, 2007;Luan et al, 2009), at least one fossil snake (Budney et al, 2006), crocodiles (e.g., Tadokoro et al, 1998;McIntosh et al, 2002), and many extinct archosaurs including some dinosaurs and early birds (e.g, Edmund, 1960), argues for its general utility in the coordination of feeding activity. It is even found in modern birds that have been manipulated to redevelop teeth (Cai et al, 2009). However, investigations on mammals (particularly primates) have theorised that balancing side muscle activity must decrease to avoid disarticulation of the working side joint (Spencer, 1998;Greaves, 1982;Throckmorton et al, 1990;Koolstra and van Eijden, 1995).…”
Section: Discussionmentioning
confidence: 98%